Human rights and development - Jones, Peris S. (Peris Sean) 1970- (Abingdon, Oxon Routledge, 2024)
This book provides a critically informed, comprehensive and multi-disciplinary entry-level account to human rights and development. The emergence of human rights within development and the evolving relationship has increasingly been brought to bear upon key debates and policies over the last couple of decades. This book provides a multi-disciplinary approach both theoretically and practically grounded and explores three over-arching questions and themes: First, why and how have human rights made this breakthrough? Second, is there agreement on human rights as a concept and how it is being used and understood within diverse development practices at global, national and local levels? Third, how we can gauge its impact upon development outcomes and what does the future hold for human rights and development? The book provides an in-depth understanding of human rights as a development challenge and delineates the responses and alternative critical approaches. Wide ranging in scope, it covers many examples of human rights within development, including global policy initiatives or vulnerable groups such as people living with HIV/AIDS, slum dwellers, victims of extra-judicial executions and indigenous peoples. This textbook will be an essential resource for social science students, particularly in the fields of development studies, human rights and geography. It should also appeal to practitioners in development and human rights"--
CONTENTS : 1. The relevance of human rights and development - - 2. Development in theory and practice - - 3. Globalisation and shifting worlds of development - - 4. Human rights controversies and convergences - - 5. Actors and institutions in human rights and development - - 6. Intersections : rights-based approaches to development - - 7. The human right to health and responses to the COVID-19 pandemic - - 8. Impact in rights based approaches : aligning actors, institutions and interests - - 9. Shaping human rights and development futures.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Human rights and globalization; Human rights; Economic development -- Social aspects; Political development -- Social aspects